Preoperative intravenous ibandronate for treating severe hypercalcemia associated with primary hyperparathyroidism: an effective and low cost - Pekkolay, Zafer; Kilinc, Faruk; Soylu, Hikmet; Balsak, Belma; Guven, Mehmet; Tuzcu, Sadiye Altun; Tuzcu, Alpaslan Kemal (Mattioli 1885, 2018)
Primary hyperparathyroidism (PHPT) is a prevalent mineral metabolism disorder usually caused by a single parathyroid adenoma. Although PHPT is the most frequent cause of hypercalcemia, severe hypercalcemia cases are rarely encountered. Severe hypercalcemia results in fatal complications unless immediately treated; moreover, it causes delays in surgery for PHPT, the primary treatment. Some patients admitted because of hypercalcemia require intravenous bisphosphonate treatment. Aimed to investigate the efficacy of intravenous ibandronate, which is a relatively cheap drug than other intravenous bisphosphonates, in the preoperative treatment of symptomatic hypercalcemia in patients with PHPT. Also, there are some difference in the total cost of treatment for patients treated with ibandronate and zolendronate. The medical records of patients operated at Dicle University Department of General Surgery between 2010 and 2017 due to PHPT were retrospectively evaluated. Patients who were admitted because of hypercalcemia associated with parathyroid adenoma and underwent minimally invasive surgery subsequent to the lowering of calcium levels via preoperative intravenous ibandronate and zolendronate were included. Totally, 20 of 167 patients received a preoperative bisphosphonate due to hypercalcemia associated with PHPT. Seven patients treated with zoledronate only. Thirteen were treated with ibandronate only. There was no difference in hypercalcemia correction between the groups. Percentage of patients with hypocalcemia was less in the ibandronate group. The hypocalcaemic period was shorter in patients receiving ibandronate. Cost of hospital stay in patients receiving ibandronate is cheaper than zolendronate (780 +/- 462 USD versus 1765 +/- 1537 USD). Ibandronate use reduces the cost of hypercalcemia treatment by 55% in comparison with zolendronic acid. Intravenous ibandronate for treating severe hypercalcemia associated with PHPT is an effective and relatively cheap drug.
Keywords: hyperparathyroidism; hypercalcemia; ibandronate